RELIABILITY AND VALIDITY OF MALAYSIA COUNSELLOR PERFORMANCE INDICATOR (M-CPI): THE COUNSELLOR VERSION - Nor Mazlina, Ghazali; Aqilah, Yusoff; Wan Marzuki, Wan Jaafar; Salleh, Amat; Edris, Aden; Azzahrah, Anuar (LEX LOCALIS, 2025)
This study was conducted to research the appropriate components to measure the performance of counsellors in Malaysia. This instrument is built in the form of self-rating. It makes it easier for counsellors to evaluate their own performance and ability over time. This is important to ensure that counsellors can carry out their duties well in looking after and helping the client's welfare, maintaining the quality and professionalism of the career as well as the individual counsellor himself. The study is oe of the rare ones found in Malaysia. In this study, a mixed method was used, namely (i) qualitative and (ii) quantitative approach. Data was obtained from 216 registered counsellors under the Malaysia Board of Counsellor using a stratified random sampling technique. The findings obtained by using Rasch Analysis, shows that this developed indicator has a high reliability value which is (.84) for person reliability and (.85) for item reliability. To know more closely, the components involved in this M-CPI consists of nine (9) constructs which are knowledge (theoretical and knowledge transfer), skills (case management, practical skills and academic /professional writing), interpersonal relationship & interaction, cultural & religiosity, professional roles and expertise, ethics and legality, attitudes and personality, referral (supervision), and articulate philosophy of profession. The findings from the scree plot also show that nine (9) constructs are suitable to be developed for M-CPI, also supported by the significant KMO value. (.000). Therefore, this proves that the components of the M-CPI are suitable and can be used to measure the performance of counsellors in Malaysia.